Investigating the Possibilities of Cash Flow Forecasts - Al-Kubati, Mohammed (2014)
This paper will use the literature to examine techniques used in practice to develop a cash flow forecast for a local firm which will remain anonymous. During the process of developing the forecasts several obstacles were encountered which required adaptation of methodology. This process resulted in developing two cash flow forecasts and a method that can be adapted by companies in similar situations. A model was also built for the client with variable inputs that can be used to examine different scenarios in the future.